Analisis dan Uji Kandungan Produk Olahan Ikan Kering yang ada di Kecamatan Salomekko Kabupaten Bone - Alimin Alimin; Hardin Hardin; Taty Sulastry (Seminar Nasional LP2M UNM, 2019)
This study is an analysis and test of dried fish content circulating in the Salomekko district of Kabpaten Bone, which aims to find out the nutritional content of dried fish in the Salomekko district of Bone Regency such as organoleptic test, formalin content test, and Pb content test, which aims to enrich information to society especially bone district society related to nutritional content contained in dried fish that they have been consuming, the results of the study show that the organoleptic test of dried fish products in terms of taste and odor is normal, for the test formalin content of dried fish product the results are negative while the contamination content test Pb in dried fish products results were not detected at 0.0074 ppm LOD where the maximum allowable condition is a maximum of 0.2 mg / kg which can be concluded that processed fish products circulating in Salomekko sub-district, bone district are very suitable for consumption.